2013
DOI: 10.1016/j.transproceed.2013.02.012
|View full text |Cite
|
Sign up to set email alerts
|

ABO-Incompatible Liver Transplantation in Acute Liver Failure: A Single Portuguese Center Study

Abstract: Introduction. ABO-incompatible liver transplantation (ABOi LT) is considered to be a rescue option in emergency transplantation. Herein, we have reported our experience with ABOi LT including long-term survival and major complications in these situations. Patient and Methods. ABOi LT was performed in cases of severe hepatic failure with imminent death. The standard immunosuppression consisted of basiliximab, corticosteroids, tacrolimus, and mycophenolate mofetil. Pretransplantation patients with anti-ABO titer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 29 publications
(57 reference statements)
0
23
0
Order By: Relevance
“…Intravenous immunoglobulin has also been used in adults that developed VBDS secondary to graftversus-host disease and for a patient with VBDS secondary to TEN but was unable to prevent progression to liver transplant in those cases. 8,9 Literature review suggested the use of TNF-a blockade. 4 Okan et al did not use TNF-a blockade but hypothesized that it could be effective because case reports showed rapid resolution of skin and mucosal damage in patients with SJS/TEN after administration of infliximab, 10,11 together with the theory of a common immunologic mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Intravenous immunoglobulin has also been used in adults that developed VBDS secondary to graftversus-host disease and for a patient with VBDS secondary to TEN but was unable to prevent progression to liver transplant in those cases. 8,9 Literature review suggested the use of TNF-a blockade. 4 Okan et al did not use TNF-a blockade but hypothesized that it could be effective because case reports showed rapid resolution of skin and mucosal damage in patients with SJS/TEN after administration of infliximab, 10,11 together with the theory of a common immunologic mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…high-risk liver recipients were still alive [174] . Kim et al [175] presented in 2014 excellent outcome results in 14 patients after ABO-I LDLT using a simplified protocol.…”
Section: Ivig and Abo Incompatible Ltmentioning
confidence: 99%
“…The implementation of beneficial immuno-regulatory properties by IVIg encouraged many transplant groups to perform ABO-I LT without complicating local graft catheterization and/or splenectomy [161,[165][166][167][168][169][170][171][172][173][174][175][176][177] . Testa et al [169] reported in 2008 on survival of 4 of 5 patients at mean of 43 mo after ABO-I LDLT following a combination of pretransplant IVIg, pre-and post-LT plasmapheresis and splenectomy.…”
Section: Ivig and Abo Incompatible Ltmentioning
confidence: 99%
See 2 more Smart Citations